2014
DOI: 10.1172/jci70698
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN signaling in CD8– DCs impairs Th1-dependent malaria immunity

Abstract: Many pathogens, including viruses, bacteria, and protozoan parasites, suppress cellular immune responses through activation of type I IFN signaling. Recent evidence suggests that immune suppression and susceptibility to the malaria parasite, Plasmodium, is mediated by type I IFN; however, it is unclear how type I IFN suppresses immunity to blood-stage Plasmodium parasites. During experimental severe malaria, CD4 + Th cell responses are suppressed, and conventional DC (cDC) function is curtailed through unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
153
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(171 citation statements)
references
References 79 publications
16
153
1
1
Order By: Relevance
“…In murine models of Plasmodium in which death is associated with immunopathology, such as P. berghei, the absence of IFNAR leads to reduced tissue pathology and reduced mortality (24,(67)(68)(69). Treatment with IFN-α or IFN-β, both prior to and during infection, however, reduces lethality, implying a role for early parasite control in contributing to lethality (70,71).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In murine models of Plasmodium in which death is associated with immunopathology, such as P. berghei, the absence of IFNAR leads to reduced tissue pathology and reduced mortality (24,(67)(68)(69). Treatment with IFN-α or IFN-β, both prior to and during infection, however, reduces lethality, implying a role for early parasite control in contributing to lethality (70,71).…”
Section: Discussionmentioning
confidence: 99%
“…To examine antigen-specific CD4 + T cells responding to infection, P. yoelii were generated that constitutively express the Lymphocytic choriomeningitis virus-derived (LCMV-derived) glycoprotein (GP) epitope (GP [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] ). This allows for the identification and analysis of antigen-specific CD4 + T cells using previously described GP66:I-A B tetramer enrichment strategies (16).…”
Section: Introductionmentioning
confidence: 99%
“…Given that the reduced parasite maturation rate was observed only a few days into the infection, we next investigated a possible role for host inflammatory responses in mediating this phenomenon (14). To begin exploring this, we first blocked type-I IFN cytokine signaling via the receptor IFNAR1, because our previous data had suggested this innate immune signaling pathway could influence circulating pRBC numbers and life stages in vivo (24) (Fig. 2C).…”
Section: Slower Maturation Of Parasites Accounts For the Majority Of mentioning
confidence: 99%
“…Importantly, Ab blockade of type I IFNR prevents disease progression and the death of infected mice. Together, these findings reveal that type I IFNs regulate parasite control by suppressing IFN-g production and suggest that blockade of type I IFN signaling during severe malaria infection may provide a novel adjunct therapy (168).…”
Section: Plasmodiummentioning
confidence: 76%
“…Interestingly, the enhanced resistance is associated with increased numbers of IFN-g-secreting CD4 + T cells (167). In a follow-up study, type I IFNs were shown to act directly on splenic conventional dendritic cells to impair their ability to phagocytose parasites and prime Th1 cells (168). In addition, deficiency in type I IFN signaling results in an increase in MHC class II expression.…”
Section: Plasmodiummentioning
confidence: 99%